2013
DOI: 10.3171/2013.4.spine12319
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and clinical evaluation of cage subsidence after stand-alone lateral interbody fusion

Abstract: Object Indirect decompression of the neural structures through interbody distraction and fusion in the lumbar spine is feasible, but cage subsidence may limit maintenance of the initial decompression. The influence of interbody cage size on subsidence and symptoms in minimally invasive lateral interbody fusion is heretofore unreported. The authors report the rate of cage subsidence after lateral interbody fusion, examine the clinical effects, and present a subsidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
308
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 381 publications
(329 citation statements)
references
References 57 publications
16
308
3
2
Order By: Relevance
“…We could not analyze the effect of cage width on endplate injury, as only 18-mm cages were available in our country; this might account for results that differed from those in previous literature 1,2) . In conclusion, intraoperative endplate injury was significantly related to bone quality, and late-onset settling was related to cage type (PEEK cage).…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…We could not analyze the effect of cage width on endplate injury, as only 18-mm cages were available in our country; this might account for results that differed from those in previous literature 1,2) . In conclusion, intraoperative endplate injury was significantly related to bone quality, and late-onset settling was related to cage type (PEEK cage).…”
Section: Discussionmentioning
confidence: 46%
“…Several factors are reported to cause cage subsidence in intervertebral fusions including LIF: reduced bone quality 12,13) , older age 13) , multilevel procedures 1,14) , narrow cage 1,2) , and use of rhBMP-2 15) . However, the abovementioned reports mixed two types of cage subsidence (intraoperative injury and postoperative spontaneous settling).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, our study was neither a large case series nor a comparative study, and some analyses were not possible (for example, analysis of the subset of patients with subsidence); nevertheless, our study is the largest case series of stand-alone treatment of degenerative scoliosis at the time of this report. Sixth, subsidence was evaluated only up to 3 months and some authors claim that later evaluation may give different results; however, our subsidence evaluation was based on a study [22] suggesting that 3-month subsidence has no significant progression with lateral placed cages. Finally, we did not report side effects related to the psoas entry and the lumbar plexus in detail because at the time of data collection we did not have a standardized method to record this variable such as that published by Le et al [21]; nevertheless, we observed no permanent deficit 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Sagittal alignment was measured by means of global lordosis and sacral slope. Subsidence was classified as described previously [22,23] in radiographs in the AP and lateral views and CT scans, based on the amount of cage subsidence into the vertebral endplates: absent or low-grade = 0% to 49%; and high-grade = 50% to 100% collapse of the level. Fusion status was determined oriented as described previously [6,14,15] in plain neutral and flexion-extension radiographs and eventually CT scans in cases with no clear conclusion on the radiographs.…”
Section: Data Collectionmentioning
confidence: 99%